Saving Face in Business Managing Cross-Cultural Interactions - Merkin, Rebecca S. (Palgrave Macmillan US, 2018)
"Professor Merkin has written a brilliant book that deftly combines two important streams of research: The work deriving from Goffman's explication of facework in communications and Hofstede's foundational work on cultural values. This book, thoroughly grounded in research, should be part of the arsenal of anybody planning for travel into another culture, whether for business or pleasure. The book is written in a style that makes it valuable to scholars and accessible to the interested lay person." -Dan Landis, Emeritus Professor of Psychology, University of Mississippi, USA "This is an essential book for scholars and practitioners interested in cultural influences on organizational facework, arriving at a time when it is needed most." -Vasyl Taras, Associate Professor of Management, University of North Carolina - Greensboro, USA "This book incorporates a theoretically grounded, yet pragmatic, accessible, clear, and well-organized, writing style that will appeal to scholars, business professionals, students, interculturalists, and world travelers alike." -Anastacia Kurylo, Assistant Professor of Communication Studies, St. Joseph's College, USA This book explains the subtle maneuvers of what researchers call "facework" and demonstrates the vital role it plays in the success or failure of cross-cultural interactions. Building on Geert Hofstede's seminal research on cultural dimensions, Merkin synthesizes more recent research in business, communication, cross-cultural psychology and sociology to offer a model for better understanding facework. Additionally, Merkin's model shows how particular communication strategies can facilitate more successful cross-cultural interactions. The first book of its kind to focus on the practical aspects of employing face-saving, it is a needed text for academics, students, and business professionals negotiating with organizations from different cultures. .